Effect of Using Dialogic Teaching Method on Seventh-grade Students’ Performance ‎in Speaking Skill - Halloush, Lana; Bani Abdelrahman, Abdallah; Abu-Dalbouh, Mousa (Jordan Journal of Educational Sciences, 2021)
This study investigated the effect of implementing dialogic teaching on Jordanian seventh-grade EFL students’ speaking skill. Two seventh-grade classrooms from Yarmouk University Model School were chosen randomly through a random sampling technique during the second semester of the academic year 2018/2019. Section A had 31 students and was assigned as the experimental group, while section b with 33 students was assigned as the control group. The experimental group was taught the speaking skill through dialogic-based instructional program, whereas the control group was taught using the conventional way as prescribed in the teacher's book. To carry out this study, an instructional program based on the speaking activities, as well as a pre-/post speaking test and an observation checklist were used after establishing their validity and reliability. The results of the study indicated that dialogic teaching contributed significantly to improving the speaking skill under study